Comparative evaluation of antimicrobial efficacy of sesame oil irrigants on Enterococcus faecalis - An in vitro study - Sameer K Jadhav; Hussain Mookhtiar; Vivek Hegde; Srilatha Shanmugsundaram (Wolters Kluwer Medknow Publications, 2020)
Introduction: During chemo-mechanical preparation, irrgants play a vital role for eradication of endodontic pathogens. Due to the shortcomings of the current irrgants used, a need has come to find out whether herbal irrigants has better cytological acceptance and whether there is a decrease in biomedical waste. With the growing trends of using herbal extracts and oils as an alternate to conventional irrigants as an antimicrobial agent, the main objective of this study was to test sesame oil itself and its combination with various agents for its antimicrobial efficacy on Enterococcus faecalis (EF). Aim: The antimicrobial efficacy of edible sesame oil and sesame oil mixture on EF using agar diffusion test. Materials and Methods: Forty-five extracted single teeth with single canal configuration were decoronated from each tooth at the cementoenamel junction and the orifices of canals were enlarged with Gates Glidden drill size number 4. EF colonies were adjusted to 1.5 × 108 colony forming unit (CFU)/ml. Crystal violet staining and observation under stereomicroscope (BX-63 Olympus DIC) were performed to check the 100% purity of culture. The inoculated specimens were divided into three groups (n = 15). The three groups are as follows: Group A was irrigated with 5.25% sodium hypochlorite (NaOCl); Group B was irrigated with edible sesame oil; and under Group C was irrigated with prepared sesame oil mixture. After 3 weeks, following the use of F4, 2 ml experimental irrigant was left undisturbed for 60 s. A volume of 20 ml of the all three irrigants were used. Absorbent paper points of sizes similar to the last apical file size used, i.e., 40.06 (F4) were placed in the canals for 5 min and transported for microbial assessment. CFUs were checked after 24 h on blood agar plates. Statistical Analysis: The intergroup statistical comparisons were performed using one-way analysis of variance (ANOVA) with Tukey's post hoc test for multiple group comparisons (P < 0.05). The intragroup comparisons were performed using r ANOVA in each study group (P < 0.01). Results: The intergroup comparison of the mean CFUs of EF on blood agar plates was significantly higher in for edible sesame oil (13.30 ± 1.64) compared to NaOCl (9.40 ± 1.24) and sesame oil mixture (7.60 ± 1.43). Conclusion: The present study confirmed the in vitro antimicrobial efficacy of prepared sesame oil mixture compared to 5.25% NaOCl and edible sesame oil.